Measuring the Effects of Narrative and Analytical Messages in Video Production - Levy G Randolph II; Ricky W Telg; Joy N Rumble; Sebastian Galindo; Angela B. Lindsey (Journal of Applied Communications, 2021)
Communication practitioners in the agriculture industry have the challenge of identifying the best way to educate consumers, and they have experienced challenges in consumer engagement. Additionally, food safety issues have continued to rise with a trend of recalls and foodborne illnesses. While the rhetoric in the agriculture industry is pointing to the need for agricultural issues to be addressed from an agriculturist sharing their stories and perspectives, there is limited research on the impact of personal narratives on attitude change and message elaboration. The purpose of this study was to determine the effects of narrative and analytical practices on elaboration, attitude, and transportation in order to better communicate about food safety practices. The researcher used Elaboration Likelihood Model, cognitive theory of multimedia learning, and narrative transportation as the theoretical framework. To test the objectives, a two (type of media: narrative and analytical) x three (length of media: short, medium and long) between-subjects factorial design was implemented. Respondents were randomly assigned to one of the experimental treatments. The respondents in this study were comprised of a non-probability sample of 712 [State] residents over the age of 18 years. Usable responses were received from 507 (71%) respondents. This study found that all videos resulted in positive attitudes toward the information and practices on the farm. Further research into narrative transportation, length of videos, and type of videos may provide an efficient approach to developing communication that narrows the educational disconnect between consumers, producers, and the production practices on the farm.
Keywords: narrative; transportation; elaboration; multimedia; video